Simplified manufacturing of advanced microstructured fibers for laser applications - Palma-Vega, G.; Hupel, C.; Nold, J.; Kuhn, S.; Limpert, Jens; Haarlammert, N.; Schreiber, T. (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
In this work, we present a simplified method for manufacturing microstructured optical fibers, which was applied for an Yb-doped pentagonal large pitch fiber (LPF). Instead of using the classical stack & draw technique, which can become time-consuming and delicate, we used a one-step structuring of the cladding via deep-hole drilling in glass. The Ybdoped core was also realized in one-step by gas phase doping via MCVD. Additional nanostructuring steps of the core material were redundant due to the high radial homogeneity of the refractive index achieved, matched with high precision to the refractive index of the glass cladding. Numerical simulations were used to verify the method and analyze the scaling of the fiber towards larger mode field diameters, which is crucial for further scaling the power in fiber lasers.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber amplifiers; Large pitch fibers; Microstructured optical fiber; Novel fiber designs; Very large mode area fiber; Yb-doped fiber